Student’s Perception on the use of Hello English Application in Improving Speaking Skills - Suyadi Suyadi; Dodi Oktariza; Dedi Efendi; Remi Fitriani; Id Ali Nady (Yayasan Adra Karima Hubbi, 2024)
Background. In the current era of globalization, the rapid development of technology greatly affects various aspects of life, including education. The Hello English application has been introduced as a learning medium to improve English speaking skills for students. Speaking is an important skill in language learning that involves an interactive process of meaning construction. Purpose. This study aims to explore students' perception of the use of the Hello English application in improving their speaking skills, as well as to find out how effective this application is in helping the teaching and learning process. Method. This study uses a quantitative approach with data collection through questionnaires distributed to students majoring in English Education at Batang Hari Jambi University. The data obtained was analyzed to determine students' perception of the use of the Hello English application. Results. The results of the study show that most students agree that the Hello English app is effective in improving their speaking skills. This application is considered practical, interesting, and able to increase students' interest in learning. The features in the application, such as speaking practice with native speakers and structured learning materials, are very helpful for students in mastering English speaking skills. Conclusion. The Hello English app has great potential in improving students' English speaking skills. The use of this application facilitates the teaching and learning process and provides an interactive and fun learning experience. However, this study has limitations in the scope of the subject which only includes English Language Education students at one university. Further research is suggested to expand the scope of the subject and deepen the understanding of the use of technology-based learning applications in various fields of education.